Effect of Self Care Education with and without Telephone Follow-Up on the Level of Hope in Renal Dialysis Patients: A Single-Blind Randomized Controlled Clinical Trial - Farzad Poorgholami; Parisa Mansoori; Zohreh Montaseri; Kazem Najafi (Shiraz University of Medical Sciences, 2016)
Background: Various strategies such as teaching self care to hemodialysis patients have been employed to increase the level of their hope. This study aimed at examining the effects of a telephone follow-up program on the level of hope in a self care education program. Methods: In this single-blind randomized controlled clinical trial, 75 hemodialysis patients, selected by convenient sampling, were randomly assigned to 3 groups (n=25 each) including a control, a self care education, or a self care education with telephone follow-up. The control group received the routine care. The self care education group received 5 instruction sessions. The telephone follow-up group had similar instructional sessions followed by telephone calls during the subsequent 2 months. Data, collected using demographic information list and Miller's hope questionnaire, were analyzed using Chi-Square, t-test, and one-way ANOVA followed by Scheffee test. Results: There was no significant difference among the scores of hope in the three groups before the intervention (P=0.40). However, after the intervention, the level of hope in the self care education group and self care education plus telephone follow-up groups were significantly higher than that of the control group (P=0.001). Moreover, the level of hope in the group with self care education plus telephone follow-up was significantly (P=0.001) more than that of the self care education group. Conclusion: Our findings indicated that teaching followed by telephone follow-up was associated with higher levels of hope. Therefore, such a strategy may be employed to improve the quality of life of patients with renal dialysis.